A Case of Dens Fracture: A Pictorial Review and Discussion. (5th August 2012) - Desai, Bobby; Slish, John; Allen, Brandon
Abstract : Dens fractures are more common in the elderly and may present after minimal trauma and with minimal neck pain. The case reports a case of a significant fracture after minimal trauma, presenting with neurologic symptoms and minimal neck pain.